(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2025)
The Educational Role of the Grace of God: A Theological Reflection.It is the aim of this paper to explore the way the theology of the grace of God is formulated in the New Testament, on the coordinates of soteriology and education. And the exploration is conducted in a conversational manner, a conversation between Paul, John, Luke and Peter, as representatives of the hermeneutical community constituted by the writers of the New Testament. In this framework, starting from the salvific role of the grace of God, the argument will continue with the educational role of the grace of God. The two roles of the grace of God, are interrelated and interconditioned, the intrinsic and indisoluble relationship between the two, being rooted in the indissolubility of Christ’s and Spirit’s Persons and works. Therefore, from the definition of the grace of God, to the coordinates of the grace of God salvific transformative work the paper will argue in the light of New Testament theology of the grace of God, the coordinates of educational transformative work of the grace of God.